Inheritance Pattern of Fruit Color and Shape in Multi-Pistil and Purple Tomato Crossing - Mahfud Mahfud; Rudi Hari Murti (AGRIVITA, Journal of Agricultural Science, 2020)
Purple tomato is the only cultivated tomato containing anthocyanin inside the fruit, while multi-pistil tomato has a unique shape and the ability to be split into smaller parts without damaging the whole fruit. Purple tomato breeding is a new direction of agriculture research to enrich antioxidant fruit, which nowadays is increasingly in demand. The objective of this research was to obtain multi-pistil tomato fruit containing anthocyanin (purple colored), also to discover the inheritance patterns and heritability of qualitative traits related to fruit color and shape obtained from multi-pistil and purple tomato crossing. This research was conducted using seven populations consisted of 2 parental populations (Multi-pistil Tomato and Purple Tomato), 2 first progeny populations (F1 and F1 Reciprocal), 2 backcross populations (BC1.1 and BC1.2), and second progeny population (F2). The result showed that pistil type, unripe fruit color, ripe fruit color, fruit shape and fruit type were inherited autosomally. The inheritance pattern of the traits followed the epistasis gene interaction with moderate to high heritability value.